The Perils of Othering and Brothering: Some Thoughts on Dying Gods in Ancient Mesopotamia - Scurlock, JoAnne (Prudence Priest Collection of the New Age Movements, Occultism, and Spiritualism Research Library, 2023)
The Frazerian Fertility Cult is the mirror image of a culture that is at the same time sex-obsessed and deeply uncomfortable on the subject. From earliest times in ancient Mesopotamia, overpopulation was a serious concern and wishes for prosperity were for "people numerous as the grass", that is, only as many as the land could support. It does not follow that Christianity has no roots in this through-the-looking-glass world. The images of rising and dying divinized mortals such as Tammuz and of dying and rising Mesopotamian planetary divinities such as Marduk (planet Jupiter), Ninurta (planet Mercury), Anu (planet Saturn) and Nergal (planet Mars) strikingly evoke images of Christ, just nothing to do with fertility as opposed to creation, life and yes, even, a sort of immanent or short term salvation. Even to outline this subject would require volumes. In this short space, I propose to offer some thoughts on this subject grounded in a scholarly lifetime of research in Assyriology. Additional Authors: Shaking the Tree, Breaking the Bough: Frazer's Golden Bough at 100 (Conference); Tully, Caroline Jane; Budin, Stephanie Lynn; University of Melbourne;
1 video file. ms150-40-009_scurlock-joanne_perils-othering_2023-02-11.mp4 .mp4 502.86 MB 527,285,407
Keywords: Dying and rising gods; Iraq--Religion; Frazer, James George, 1854-1941. Golden bough. Abridged; Video recordings; Conference papers and proceedings; Literary criticism